Innovative clothing system for protection against perforation - Gilda Santos; Rita Marques; Miguel Pinto; Francisco Pinheiro; Patricia Ferreira (Communications in Development and Assembling of Textile Products)
Opuntia ficus-indica is a cactus species that has a large potential in several applications. Despite its enormous potential, the production process is still a concern. The harvest process is still mostly manual and implies a dangerous exposure of the human being not only to harsh environmental conditions such as high temperatures but also to the big and resistant spines of the Opuntia ficus-indica. To fulfill the lack of suitable protection equipment for this specific activity, emerged a project with the aim of producing an innovative clothing system composed by textile structures that can act as a barrier to spines and glochids without compromising breathability and presenting a suitable fitting, ergonomics and freedom of movements. This paper will focus on the development of a multilayer clothing system in which the outer layer provide protection against perforation and the inner layer acts like a second skin providing thermal comfort and freedom of movement, so the producers can withstand high temperatures. Concerning the inner layer, several textile structures were developed to analyze the impact on breathability, moisture management and thermal regulation. For the outer layer more than 20 fabrics were developed and submitted to laboratory tests to study their perforation and tearing resistance (according to EN 388).Afterward two structures were selected to proceed and new finishing’s were developed to prevent the adhesion of the glochids to the textile substrate and simultaneously to give water repellency. Results achieved for the clothing solution from laboratory and field tests with end-users, will be presented.